EFEKTIVITAS MODEL PEMBELAJARAN ENVIRONMENTAL LEARNING TERHADAP KEMAMPUAN MENULIS KREATIF PANTUN PESERTA DIDIK KELAS VII DENGAN BERBANTUAN APLIKASI CANVA SMPN 6 LEMBANG: Artikel Penelitian Skripsi - Mita Zakia Agliani; Dindin Muhammad Zainal Muhyi; Meity Suratiningsih (STKIP Subang, 2023)
The low context of students' writing abilities, especially in creative forms like composing traditional rhyming quatrains (pantun), is caused by the students' lack of self-confidence in expressing their creative ideas, as well as feelings of boredom and disinterest in the classroom due to the limited variation and innovation in the instructional models employed by educators. Therefore, in this study, one proposed approach to address this issue is the implementation of an environmental learning instructional model.The method utilized for this research is a quasi-experimental design. Data was gathered through trial tests and data analysis. Pre-test and post-test data were collected from both the experimental and control groups of seventh-grade students at SMPN 6 Lembang. The research findings reveal several significant observations: Firstly, a notable improvement in creative writing abilities concerning traditional rhyming quatrains was observed in the seventh-grade class, particularly within the experimental group. The average scores between the pre-test and post-test in the experimental group increased from 64.5 to 82.33, while in the control group, the scores increased from 59.833 to 74.66. Secondly, students in the experimental group exhibited enhanced mastery of creative writing skills in traditional rhyming quatrains, especially with the aid of the environmental learning instructional model. In this context, the model demonstrated its effectiveness in enhancing the creative writing abilities of the students. Lastly, a significant disparity in the utilization of the Canva application within the instructional models was observed between the experimental group and the control group. Statistical table outputs indicate an Asymp.sig value of 0.001, which is lower than the significance level of 0.05. This signifies a substantial difference in the effectiveness of the Canva application in enhancing creative writing abilities in traditional rhyming quatrains between the experimental group and the control group. Consequently, the results of this research substantiate the efficacy of the environmental learning instructional model in conjunction with the Canva application to foster the development of creative writing abilities in traditional rhyming quatrains among seventh-grade students Keywords: Writing, Environmental Learning Model, Pantun, Canva.